Solar Photovoltaic (Pv) System For Soil Moisture Level Detector - Ithin, Muhammad Naqib; Jumaat, Siti Amely; Mohamad Nor, Ahmad Fateh; Ismail, Muhammad Nafis; Salimin, Suriana; Ching, Kok Boon (Gae, 2025)
This paper is to aim in designing a system which is capable of detecting moisture level in the soil and capable of taking the decision of switching ON/OFF water pump in irrigation system. The microcontroller, Arduino forms the heart of the device for detecting the moisture in the soil and is programmed with the Arduino software. This project involves the development an automatic watering system that utilizes sensor that determines soil moisture level and water level designator additionally its pumping system that aims to distribute the needed water predicated on the assigned soil moisture value. The reading of the soil sensor is above 70%, the water pump will turn off, and when it is below 70%, the water pump will turn on until the soil sensor reading returns to normal. As a result of this project, the prototype successfully operated in line with the simulation. As the results at 1pm, 4th June 2024 with temperature 28oC, humidity is 73% the higher volume of water is 5.5ml with 5-minute water pumps was on. Next, the results for solar PV as main supply, the high output voltage is 14.8V at 2pm, 14th and 16th June 2024. As conclusion, this project has successfully achieved all the stated objectives and performs its desired functions, such as measuring humidity levels, temperature values, and soil moisture levels. This innovative system enhances plant care by providing users with real-time data and potential also ensuring optimal growing conditions and convenience for plant conditions.